2006
DOI: 10.1002/jca.20079
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytapheresis in the treatment of psoriasis vulgaris

Abstract: Psoriasis is a common autoimmune chronic inflammatory skin disease that affects approximately 2% of the world's population; fundamental for its immunopathogenic mechanism is secretion of type 1 (Th1) cytokines by T cells and their activation. Since cytapheresis has been widely applied to autoimmune disorders, emphasizing the recently reported results of granulocyte and monocyte adsorption apheresis in psoriasis, a small series of psoriasis vulgaris (PV) patients underwent lymphocytapheresis (LCA) with the aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Lymphoplasmapheresis (LPE) is a combined technique that integrates both TPE and lymphocytapheresis, resulting in both pathogenic antibody removal and immunoregulation (12). In previous studies, lymphocytapheresis was shown to be efficacious in the treatment of autoimmune disorders including psoriasis vulgaris and multiple sclerosis (13,14). Recently, LPE was reported to be effective in patients with Guillain-Barre syndrome by directly removing immunoglobulins, complements, monocytes, and fibrinogen, as well as regulating lymphocyte subsets in the peripheral blood (15).…”
Section: Introductionmentioning
confidence: 99%
“…Lymphoplasmapheresis (LPE) is a combined technique that integrates both TPE and lymphocytapheresis, resulting in both pathogenic antibody removal and immunoregulation (12). In previous studies, lymphocytapheresis was shown to be efficacious in the treatment of autoimmune disorders including psoriasis vulgaris and multiple sclerosis (13,14). Recently, LPE was reported to be effective in patients with Guillain-Barre syndrome by directly removing immunoglobulins, complements, monocytes, and fibrinogen, as well as regulating lymphocyte subsets in the peripheral blood (15).…”
Section: Introductionmentioning
confidence: 99%
“…Cytapheresis has been successfully applied in rheumatoid arthritis, systemic lupus erythematosus, and inflammatory bowel disease (7–9). In dermatology, patients with psoriasis and pyoderma gangrenosum have been successfully subjected to leukocytpheresis (10,11).…”
mentioning
confidence: 99%
“…Fundamental for its immunopathogenic mechanism is the secretion of type 1 (Th 1) cytokines by T cells and their activation. 92 Cytokines are intercellular molecules that have an important role in the development and maintenance of cutaneous inflammation. 93 The indication for TPE in psoriasis vulgaris is also based on the presumption of immunopathogenesis.…”
Section: Methodsmentioning
confidence: 99%
“…But the skin lesions did not respond to photopheresis. 92,100 However, blocking TNF-α by infliximab or etanercept has shown particular promise, especially in the management of psoriasis. But further studies to address its mechanism of action and potential long-term side effects are needed.…”
Section: Methodsmentioning
confidence: 99%